2003
DOI: 10.5328/jver28.3.185
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Supervisor and Employee Perceptions of Work Attitudes in Information Age Manufacturing Industries

Abstract: publishes refereed articles that examine research and research-related topics in vocational education, career and technical education, preparation for work, and the workplace. The JVER Editorial Board is committed to publishing scholarly work that represents a variety of conceptual and methodological bases. Submission of manuscripts representing one of the following styles is encouraged: (a) empirically-based manuscripts that report results of original research, either quantitative or qualitative, (b) reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 61 publications
2
7
1
Order By: Relevance
“…Instead, men employees gave higher ratings on all of the five work value factors, which indicated that men employees had more positive feelings on work values than did women employees. This result differs greatly from many of the previous findings that females are more likely to exhibit better work attitudes than their male counterparts (Azam, 2002;Furnham and Muhiudeen, 1984;Hill, 1997;Petty and Hill, 1994).…”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…Instead, men employees gave higher ratings on all of the five work value factors, which indicated that men employees had more positive feelings on work values than did women employees. This result differs greatly from many of the previous findings that females are more likely to exhibit better work attitudes than their male counterparts (Azam, 2002;Furnham and Muhiudeen, 1984;Hill, 1997;Petty and Hill, 1994).…”
Section: Resultscontrasting
confidence: 83%
“…One trend in the labor force has been the increase of information age jobs that are high-discretion positions that require considerable thinking and decision-making on the part of workers (Miller, 1986). This is in contrast to more traditional industrial age jobs that tend to require obedience rather than decision-making skills (Azam, 2002). Due to the large impact that these information age workers have on the organization, positive work attitudes may be more important than ever before.…”
Section: Education and Work Valuesmentioning
confidence: 88%
See 2 more Smart Citations
“…Using the OWEI, Minton (1997) found a significant difference between employers' expectations of work ethic and the self-perceived work ethic of secondary school students. In a recent study, Azam (2002) found significant differences between employees' self-perceived work attitudes and their work attitudes as rated by their supervisors. In the same study, significant differences in work attitudes were obtained between information and noninformation employees.…”
mentioning
confidence: 94%